Entrada em domicílio em caso de crimes de drogas: Geolocalizaç\~ao e análise quantitativa de dados a partir de processos dos Tribunais da Justiça estadual brasileira - Rafael de Deus Garcia; Victor Dantas de Maio Martinez; Natalia Cardoso Amorim Maciel; Andréia de Oliveira Macêdo; Hugo Homem Macedo; Karolina Chacon Armstrong; Milena Karla Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The present work aims to analyze characteristics of home entries in criminal proceedings involving drug crimes, in order to determine whether home policing, within the context of drug policies, selectively or geographically segregates defendants who face the criminal justice system. Based on data from the research study "Profile of Defendants and Evidence Production in Criminal Actions for Drug Trafficking," conducted by the Institute for Applied Economic Research (Ipea), the right to inviolability of the home is discussed in light of empirical data on the context of home entries - which occur in nearly half of the cases, often without clear documented motivation. To deepen the study, the capital city with the highest number of home entries in each Brazilian region was identified - Brasília, Curitiba, Fortaleza, Manaus e Rio de Janeiro -, aiming to gather sociodemographic information about the neighborhoods where the inviolability of the home is undermined. The results reveal that wealthier neighborhoods and those with predominantly white populations are almost immune to home entries, which are substantially concentrated in poorer neighborhoods and in those with predominantly black or minority white populations. Confirming the hypothesis of criminal selectivity, it is concluded that stricter judicial authorization is necessary for general home entries, in order to preserve the constitutionally fundamental right of inviolability of the home.
Keywords: K14; K38; K41; K42; 330; Drug policies; police home entry; empirical legal research; georeferencing; criminal selectivity